PELATIHAN PEMBUATAN PESTISIDA NABATI DAUN PEPAYA SEBAGAI ALTERNATIF PENGENDALIAN HAMA PADA KELOMPOK TANI DESA LESANPURO - Arifah, Nur; Ramadoni, Elmikosari; Albany, Latif Wanda; 'Ulyan, Mohammad (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Pest and disease control carried out by most farmers is by using chemical pesticides, so an alternative pest and disease control method that is more environmentally friendly is needed, such as botanical pesticides. Botanical pesticides are pesticides that come from plants, namely papaya leaves, which are relatively easy to make and easy to decompose. The aim of this outreach is through Real Work Lectures (KKN) to provide an understanding of the importance of using botanical pesticides to control pests and explain the steps for making papaya leaf botanical pesticides. The methods used in this activity are observation, presentation of material, and making botanical pesticides. The results of the outreach activities on plant pesticides were carried out to provide understanding and insight regarding the use of natural plants as pesticides to farmers.